Methods for Evapotranspiration in Hydrological Models - Prof. Shishira Kanta Behera, Prof. Chapala Bahidar (International Journal of Modern Agriculture, 2020)
Current evapotranspiration is a basic hydrologic cycle mechanism and is an only concept related to the balance of land surface water and land surface resources. A key role in simulating the hydrological effect of climate change is evapotranspiration, and an analysis of the methods of evapotranspiration measurement in hydrological models is important. This paper summarizes first the evaluation methods of evapotranspiration applied in hydrological models and then classifies them in their mechanisms into integrated conversion methods and classification methods. In hydrological models integrated converting methods are usually used and there are two differences: The first is the evaporation estimation of potential methods, while the second one defines the relation between the evaporation potential and actual evapotranspiration. In hydrological models simplified empirical procedures for the calculation of the potential and actual evapotranspiration are widely utilized due to greater information requirements of the Penman-Monteith process and the existing data uncertainty. Depending on the complexity of the hydrological model and on the significance and complexity of selecting the most suitable evapotranspiration methods, various evapotranspiration estimation methods are used. Finally, this paper illustrates the future development patterns of hydrological modelling approaches for estimating evapotranspiration.